2015
DOI: 10.1161/strokeaha.115.008891
|View full text |Cite
|
Sign up to set email alerts
|

Early Recurrence and Cerebral Bleeding in Patients With Acute Ischemic Stroke and Atrial Fibrillation

Abstract: Background and Purpose— The best time for administering anticoagulation therapy in acute cardioembolic stroke remains unclear. This prospective cohort study of patients with acute stroke and atrial fibrillation, evaluated (1) the risk of recurrent ischemic event and severe bleeding; (2) the risk factors for recurrence and bleeding; and (3) the risks of recurrence and bleeding associated with anticoagulant therapy and its starting time after the acute stroke. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
194
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 247 publications
(216 citation statements)
references
References 19 publications
10
194
2
10
Order By: Relevance
“…Thus, such a decision hinges on the assessment of the competing risks of early thromboembolic recurrences and hemorrhagic transformation 3. Data from the RAF (Early Recurrence and Cerebral Bleeding in Patients With Acute Ischemic Stroke and Atrial Fibrillation) study suggested that the optimal time for initiating anticoagulation treatment for secondary stroke prevention may be 4 to 14 days from stroke onset 4. Moreover, patients treated with oral anticoagulants alone had better outcomes compared with patients treated with low‐molecular‐weight heparins (LMWHs) alone or before oral anticoagulants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, such a decision hinges on the assessment of the competing risks of early thromboembolic recurrences and hemorrhagic transformation 3. Data from the RAF (Early Recurrence and Cerebral Bleeding in Patients With Acute Ischemic Stroke and Atrial Fibrillation) study suggested that the optimal time for initiating anticoagulation treatment for secondary stroke prevention may be 4 to 14 days from stroke onset 4. Moreover, patients treated with oral anticoagulants alone had better outcomes compared with patients treated with low‐molecular‐weight heparins (LMWHs) alone or before oral anticoagulants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients treated with oral anticoagulants alone had better outcomes compared with patients treated with low‐molecular‐weight heparins (LMWHs) alone or before oral anticoagulants. In the RAF study, with enrollment from January 2012 to March 2014, <10% of the patients were treated with non–vitamin K oral anticoagulants (NOACs) 4. Observational studies reported that, if NOACs are started early after an index event, the risk of intracranial bleeding appears to be low 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…As advanced age is not a contraindication to the use of rivaroxaban [14], he was treated with this DOAC at the dose of 15 mg/die starting 5 days after the index event, despite the presence of intraventricular bleeding occurred after the thrombolytic therapy for the first event. Our results are even more encouraging given that randomized clinical trials with DOACs have excluded acute ischemic stroke patients, and the safety of DOAC administration soon after an index event has only been addressed by observational, prospective, and non-randomized studies [8][9][10][11][12][13]. In particular, in two prospective studies, the treatment with DOACs was commenced after a mean time of four and five days from the index event and no intracranial bleeding was observed during hospitalization [8,13], suggesting the safety of the early use of DOACs after an ischemic episode.…”
Section: Discussionmentioning
confidence: 71%
“…However, randomized clinical trials on DOACs have systematically excluded patients with recent ischemic stroke (<7 days) in whom the risk of sHT is higher [4][5][6][7]. Despite the lack of conclusive clinical evidence, the available data from observational, longitudinal studies suggest that the early use of DOACs is safe and might reduce the risk of sHT [8][9][10][11][12][13]. Therefore, in clinical practice, these agents are perceived as safe and increasingly used even during the first days after ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Однако при от-дельной оценке данной группы пациентов бы-ло выявлено, что повторные НМК у этой кате-гории за 10 лет наблюдения были отмечены у 28,6%. Перенесенный инсульт в анамнезе явля-ется независимым фактором риска повторных НМК [1][2][3]19] Так, по данным работ, посвя-щенных краткосрочному прогнозу больных с ФП, перенесших острый инсульт, выявлено, что частота повторных инсультов достигает 7,6-10% в течение 90 дней [6,[20][21]. Среди наших 49 пациентов, перенесших инсульты до момента включения в исследование, у 20 (40,8%) инсульт произошел в течение послед-него года, что делает этих пациентов наиболее уязвимыми в отношении повторных мозговых катастроф.…”
Section: Discussionunclassified